2007
DOI: 10.1016/s0929-6646(09)60298-9
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal and Multiple Mesenteric Calcifying Fibrous Pseudotumor Induced Jejunojejunal Intussusception

Abstract: We describe here a patient with an unusual presentation--mesenteric calcifying fibrous pseudotumor in association with jejunojejunal intussusception. This 25-year-old woman came to our emergency department with severe abdominal distension and intermittent epigastric cramping pain. She was found to have rebound tenderness and an ill-defined mass palpable in her lower abdomen. Abdominal computed tomography revealed an inhomogeneous soft tissue mass with target sign and intussusception of small intestine was susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…However, it may be difficult to clean up minor tumors of <2 mm in size at multiple sites and consequently these tumors will be left untreated, especially when the patient is without any discomfort. 4 Sleigh et al suggested using repeated CT to monitor the tumor in the pleural or the mediastinal location. 14 In our case, we used gastroscopy to monitor CFT in the GI tract, because endoscopy is more efficient and provides clearer demonstration than CT for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be difficult to clean up minor tumors of <2 mm in size at multiple sites and consequently these tumors will be left untreated, especially when the patient is without any discomfort. 4 Sleigh et al suggested using repeated CT to monitor the tumor in the pleural or the mediastinal location. 14 In our case, we used gastroscopy to monitor CFT in the GI tract, because endoscopy is more efficient and provides clearer demonstration than CT for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly involved sites are the stomach [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and small intestine. 3,4,6,14,[17][18][19][20][21][22][23][24][25] Three examples in the large intestine exist 14,17,26 and a single case in the esophagus. 27 Patient age ranges from 5 to 77 years, with a mean of 40.8 years; no sex predilection is evident.…”
Section: Clinical and Imaging Findingsmentioning
confidence: 99%
“…Multiple lesions were documented in 11 of 43 patients, many of which had concurrent extra-GI involvement, with the most common site being the mesentery. 14,17,19,20,[22][23][24][25] One author reported GI CFTs occurring in siblings. 19 Although most are discovered incidentally, CFTs in the GI tract can present in unique ways.…”
Section: Clinical and Imaging Findingsmentioning
confidence: 99%
See 2 more Smart Citations